Neoplasias escamosas intra-epiteliais e invasoras da vulva : expressão de receptores de estrógeno e de progesterona, de p53 e de Ki-67(MIB1) segundo a progressão tumoral - Arruda, Luciana Gomes da Rocha de (2004)
Vulvar cancer, although a rare neoplasia, implicates in serious problems due to the extensive surgery and consequent mutilation. It affects primarily elderly women, and has been more frequent in young patients associated with HPV infection. With the aim to identify pertaining factors evaluated in the genesis and progression of this tumor, an evaluation was carried out by immunohistochemistry (StrepABC), to identify the presence of estrogen and progesterone receptor in the epithelia and stroma of 45 vulvar lesions, of which 22 are invasive squamous cell carcinomas (ISCC), 12 are high-grade intraepithelial lesions (HSIL) and 11 are low-grade intraepithelial lesions (LSIL). Furthermore p53 protein expression and the cell proliferating index, through MIB1, were evaluated. The cases came from the Cancer Institute of Ceará (CIC), the Hamilton Monteiro Laboratory of Pathology (HML) and the Laboratory of Pathology of UFC. A descriptive analysis of the parameters and their correlations were carried out with a statistical significance level of at least 95% (p ≤ 0,05). Results and inferences: 1 - Age: The ISCC occurred between the ages of 34 and 76 years (average 58.59 and median 60.5), the HSIL ranges from 18 to 59 years (average 40,91 and median 42) and the LSIL-papilloma within the ages of 18-58 (average 32.63 and median 32), in the expected age groups and interval ranges, according to the natural history reports of such lesions, highlighting the growing of ISCC in patients ever younger. 2 - Hormonal receptor: The nuclear receptors of estrogen and progesterone were detected in the three groups analyzed, with a growing tendency of tumoral progression, however without significant statistical correlation in the epithelia level. Thus they cannot be considered a predictive and prognostic factor in the follow-up of these lesions. However in the stroma the presence of nuclear immunostain is significant (more with ER) in the HSIL and ISCC, which can be important to the tumor growth. The high and frequent immunostain was also observed in the cytoplasm of keratinocytes of in situ carcinomas and keratinizing invasive squamous cell carcinoma. These findings will be evaluated in the future. 3 - p53: The expression of p53 was detected in all groups, ISCC (68,18%), HSIL (66,66%) and LSIL (63,63%), having more frequent high scores in carcinomas (53,33%) than in LSIL (0,00%). The behavior of HSIL is similar to the behavior of ISCC. It is evident that there is an accumulation alteration of p53 with the tumoral progression. 4 - MIB1- There were significant differences between ISCC and LSIL (p=0,00), also among HSIL and LSIL (p=0,03). There was no significant difference between ISCC and HSIL. This expresses the tendency of high index cell proliferation with tumoral progression. In addition, the independence of the variables, MIB1 and p53, were verified.